Did a digital quality of life (QOL) assessment and practice support system in home health care improve the QOL of older adults living with life-limiting conditions and of their family caregivers? A mixed-methods pragmatic randomized controlled trial - Richard Sawatzky; Kara Schick-Makaroff; Pamela A. Ratner; Jae-Yung Kwon; David G. T. Whitehurst; Joakim Öhlén; Alies Maybee; Kelli Stajduhar; Lisa Zetes-Zanatta; S. Robin Cohen (PLoS ONE, 2025)
We aimed to improve the quality of life (QOL) of homecare patients (≥ 55 years of age) who had chronic life-limiting conditions and that of their family caregivers by making QOL assessment data available via a digital QOL and practice support system (QPSS). We hypothesized that access to QPSS data in home health care would result in improved QOL for patients or their family caregivers. We further sought to understand how to integrate the use of QOL information into home health care. Our mixed-methods study, including a pragmatic randomized controlled trial (PrCT; registered at ClinicalTrials.gov #NCT02940951), was conducted with nine home healthcare teams in Canadian urban areas. The qualitative research included focus groups and interviews with home healthcare teams (N = 118) to determine how to integrate the QPSS into their practice. Participating homecare patients were assigned to an intervention group (N = 166), where home healthcare teams had access to patients’ and their family caregivers’ QOL data via the QPSS, or a usual care group (N = 165). Where possible, one family caregiver per patient was recruited (intervention N = 62; usual care N = 51). Primary outcomes, measured every two months for one year, were patients’ and family caregivers’ QOL trajectories. Longitudinal structural equation models were used to compare the trajectories. The home healthcare teams preferred to have QOL scores presented as tables and graphs, with family caregivers’ data linked to each patient. Despite the enthusiasm expressed by the home healthcare teams, and efforts to satisfy their preferences, they infrequently accessed the QOL information. While we observed substantial individual-level variability in patients’ and family caregivers’ QOL trajectories, the average trajectories for the PrCT groups were similar. Making QOL assessment data available via a digital platform may not be sufficient to achieve measurable improvements for patients and family caregivers.